Cleavage of CD14 and LBP by a protease from Prevotella intermedia - Deschner, James (Arch Microbiol, 2003)
Periodontitis is an inflammatory disease caused by subgingival microorganisms and their components, such as lipopolysaccharide (LPS). Responses of the host to LPS are mediated by CD14 and LPS-binding protein (LBP). In this study, it was determined that proteases from a periodontal pathogen, Prevotella intermedia, cleave CD14 and LBP, and thereby modulate the virulence of LPS. Culture supernatants from two strains of P. intermedia (ATCC 25611 and 25261) cleaved CD14 and LBP in a concentration-dependent manner. Zymographic and molecular mass analysis revealed the presence of a membrane-associated, 170-kDa, monomeric protease. Class-specific inhibitors and stimulators demonstrated that this enzyme is a metal-requiring, thiol-activated, cysteine protease. The protease was stable over a wide range of temperatures (4–56 °C) and pH values (4.5–8.5). This enzyme also decreased the expression of interleukin-1β (IL-1β)-specific mRNA in the LPS-activated macrophage-like cell lines U937 and THP-1 in a concentration-dependent manner, indicating that it also cleaves membrane-associated CD14. Furthermore, addition of soluble CD14 abrogated protease-mediated inhibition of IL-1 mRNA expression induced by LPS. The observations suggest that proteolysis of CD14 and LBP by P. intermedia protease might modulate the virulence of LPS at sites of periodontal infections.